2020
DOI: 10.18203/2320-6012.ijrms20202267
|View full text |Cite
|
Sign up to set email alerts
|

Open-angle glaucoma in diabetic patients’ prevalence and risk factors: a cross-sectional study in Sudan

Abstract: Background: Diabetic patients are at increased risk of glaucoma compared to the general population. Risk factors for glaucoma that is specific to diabetic patients include increased IOP, retinopathy and neovascular changes and years since diagnosis of diabetes. This cross-sectional study aims to report on the prevalence of glaucoma in diabetic patients in community diabetes centre in Sudan and examine associations with previously reported risk factors.Methods: A cross-sectional study was carried out in Omdurma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Patients with a positive family history of glaucoma were 3.72 times more likely to develop glaucoma. Studies in Australia [28,29], Sub-Saharan Africa [11], and Sudan [36] also found similar results. The reason might be due to hereditary factors.…”
Section: Discussionsupporting
confidence: 57%
“…Patients with a positive family history of glaucoma were 3.72 times more likely to develop glaucoma. Studies in Australia [28,29], Sub-Saharan Africa [11], and Sudan [36] also found similar results. The reason might be due to hereditary factors.…”
Section: Discussionsupporting
confidence: 57%
“…6 Several studies suggest that genetic abnormality is also implicated in glaucoma cases even in the diabetic population, but in such studies, the population is not compared to non-diabetic population. 15 Three systematic reviews examined the associations between diabetes and glaucoma. [7][8][9] Pooled analysis from those studies reported different OR 1.37, (95% CI=0.72-2.02), OR=1.36, (95% CI=1.25-1.50) and OR=1.48, (95% CI=1.29-1.71).…”
Section: Pathophysiologic Changes Of Diabetic Retinopathy and Glaucommentioning
confidence: 99%